Understanding the Relationship Between Knowledge, Vaginal Hygiene Practices, and Vaginal Discharge in Adolescents - kenzi, Sofia; Anastasya, Shafira (International Journal on Health and Medical Sciences, 2024)
Understanding the Relationship Between Knowledge, Vaginal Hygiene Practices, and Vaginal Discharge in Adolescents. This study aims to investigate the relationship between knowledge levels, vaginal hygiene practices, and vaginal discharge among adolescents, with a focus on identifying factors influencing vaginal health outcomes within this demographic group. A cross-sectional study design was employed, involving the recruitment of female adolescents aged 13 to 19 years from diverse settings such as schools, community centers, and healthcare facilities. Data were collected through structured surveys, clinical assessments, and standardized instruments, capturing information on knowledge levels, hygiene practices, and types of vaginal discharge. Descriptive statistics, graphical representations, and inferential statistics, including correlation analysis, regression analysis, and mediation/moderation analyses, were used to analyze the data and interpret the findings. The findings revealed positive correlations between knowledge levels and adherence to recommended hygiene practices, as well as an inverse relationship between knowledge levels and the prevalence of abnormal vaginal discharge among adolescents. Vaginal hygiene practices were found to partially mediate the relationship between knowledge levels and vaginal discharge, highlighting their importance in translating knowledge into actionable strategies for maintaining vaginal health. Socio-cultural factors were identified as moderators of these relationships, underscoring the need for culturally sensitive interventions that address diverse cultural contexts and socio-economic disparities.